2014
DOI: 10.1007/s12603-013-0410-3
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the SARC-F scale on screening sarcopenia and physical disability in the Chinese older people

Abstract: The SARC-F scale can identify old Chinese people with impaired physical function who may suffered from sarcopenia. SARC-F judgment reflects fear of falling, indicates the hospitalization events and is associated with ability of daily life. Thus, SARC-F may be a simple and useful tool for screening individuals with impaired physical function. Further studies on SARC-F in Chinese people would be worthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 24 publications
1
59
0
Order By: Relevance
“…Like the others in this Asian population, it had modest predictive value for 4‐year physical limitation. Cao et al have also provided evidence for validity of the SARC‐F.…”
Section: Can Sarcopenia Be Predicted By a Questionnaire Without Measumentioning
confidence: 97%
“…Like the others in this Asian population, it had modest predictive value for 4‐year physical limitation. Cao et al have also provided evidence for validity of the SARC‐F.…”
Section: Can Sarcopenia Be Predicted By a Questionnaire Without Measumentioning
confidence: 97%
“…For both men and women, a moderate negative correlation was seen between SARC‐F‐J and TMIG‐IC and FES, whereas a moderate positive correlation was seen between SARC‐F‐J and CL. In previous studies, correlations were reported between sarcopenia diagnosed with SARC‐F and decline in physical function, decline in ADL, and decline in FES score . TMIG‐IC and CL are questionnaires that measure medical conditions such as decline in ADL and frailty closely related to sarcopenia .…”
Section: Discussionmentioning
confidence: 99%
“…The SARC-F 14e16 has also been developed as a possible rapid test for sarcopenia in individuals with impaired physical function. 38 Nonetheless, these 2 screening tools have not been tested to predict functional outcomes either in outpatients or in inpatients. Both of these methods potentially could be used in clinical practice to allow early detection and of probable sarcopenia and, if present, early interventions to reduce the related burden (eg, functional decline and fall risk).…”
Section: Discussionmentioning
confidence: 99%